Modelling of a novel hydro-pneumatic accumulator for large-scale offshore energy storage applications. (December 2017) - Buhagiar, Daniel; Sant, Tonio
Highlights: A novel hydro-pneumatic energy storage device is presented. This is based on an accumulator with an external chamber that is integrated into a floating platform. A thermodynamic model of the system is derived to calculate the efficiency and illustrate the pressure response. Results show that the system is stable under a variety of meteorological conditions and has a relatively high efficiency. Abstract: Despite the ability of accumulators to smooth out fluctuations in small-scale hydraulic circuits, their use in multi-megawatt power transmission systems remains limited. This is due to the large pressure variations that they experience as their state-of-charge changes when their energy capacity is large. The present work highlights an approach whereby the pressure fluctuations are absorbed by a larger external volume of compressed air. This system has been integrated into a novel floating platform for offshore applications. A thermodynamic model of the gas compression process is developed in order to observe temperature and pressure fluctuations. A brief parametric analysis is undertaken to illustrate the effect of critical system dimensions. This comprises the effect of the external volume with respect to the accumulator volume and the diameter of the umbilical connecting the two components. The system is also simulated in different climates to observe the interaction between the external seawater temperature and the internal gas thermodynamics. A full charge-discharge cycle is simulated and results indicate that around 95% of the energy can be recovered after being stored for a 24-h period. The operational efficiency for a stochastic energy input was also computed and found to be relatively high. Electrical round-trip efficiency was found to be comparable to adiabatic and near-isothermal CAES, but the system can be more advantageous when integrated into the generation-side. The key attribute is the minimization of pressure fluctuations, which results in minimal deviations from the equilibrium temperature. This reduces thermal losses to the surroundings and results in a highly efficient energy storage system.